Mapas conceituais nos cursos de formação de professores da UFS - Sousa, Glauber Santana de (2010)
It is known that old teaching strategies together with traditional pedagogical paradigm are insufficient to guarantee that learning really occur based on the new model of society. The professors need to ensure the Significant Learning and a way to achieve this goal is through Conceptual Maps (CM). Thus, this dissertation aimed to find out how Conceptual Maps are a part of the initial formation of basic education professors from UFS courses. Qualitative methodology was used through the application of questionnaires and interviews. Nine interviews from professors that teach pedagogical disciplines were analyzed. Most of them indicated the use of CM in a search for differ their teaching strategies in order to promote the Significant Learning in the classroom. The maps main contributions on the courses were: the facility for learning concepts, which helps future teachers to better master the content and instrumentation for the exercise of professional practice using one of the resources present in current textbooks of basic education. This strategy was perceived as favorable to the development of teaching practice that has brought improvements to the teaching and learning process of some pedagogical disciplines from UFS programs.